Analysis of the flow systematics in Au+Au collisions - Veselsky, M.; Ma, Yu-Gang; Souliotis, G. A. (HNPS Advances in Nuclear Physics, 2019)
The new implementation of the Boltzmann-Uhling-Uhlenbeck equation, the VdWBUU simulation (with EoS-dependent in-medium nucleon-nucleon cross sections) appears to reproduce the flow observables in the Au+Au collisions in the energy range from 400 AMeV to 10 AGeV. The range of the feasible stiffness of the EoS can be identified, based on the analysis presented here, as encompassing compressibilities starting from 250-260 MeV and above, and thus consistent with the results of re-analysis of the giant monopole resonance data (250-310 MeV). Using that additional constraint, the range of feasible values of the stiffness of density dependence can be set as γ=1−1.25, with the value γ=1 appearing as as a global value of stiffness of the symmetry energy feasible over the whole range of constrained compressibilities. The implementation of BUU with the free nucleon-nucleon cross sections can not describe correctly the global trends of flow observables.